Open-top TiO2 nanotube arrays with enhanced photovoltaic and photochemical performances via a micromechanical cleavage approach. Issue 27 (18th June 2015) - Liao, Yulong; Zhang, Dainan; Wang, Qi; Wen, Tianlong; Jia, Lijun; Zhong, Zhiyong; Bai, Feiming; Tang, Longhuang; Que, Wenxiu; Zhang, Huaiwu
Abstract : Easy removal of the disordered nanograss top-layer through a "scotch-tape method" with enhanced photoelectronic performances. Abstract : Anodic growth of TiO2 nanotube (NT) arrays has been proved to be very promising for energy conversion applications, e.g. in photovoltaic devices and fuel cells. However, disordered "nano-grass" layers were always found on the top of the anodic TiO2 NT arrays. In this paper, we demonstrate a novel and simple method using a micromechanical cleavage technique to peel off the disordered nanograss layer. Using this method, ∼1 × 1.5 cm −2 of uncapped TiO2 NT arrays with a high-aspect ratio can be easily obtained. The results further indicate that the treatment can improve the photovoltaic and photochemical performances. After the treatment, the conversion efficiency ( η ) of the dye sensitized solar cells (DSSCs) increased by 29.3%. This work facilitates the growth and applications of high aspect-ratio anodic TiO2 NT arrays in related devices and systems.